Economic design of sleeve rotor induction motor using rotor ends - Omar S. Daif; M. Helmy Abd El-Raouf; Mohamed Adel Esmaeel; Abd Elsamie B. Kotb (Institute of Advanced Engineering and Science, 2022)
In this paper, the field analysis of the sleeve rotor induction motor (IM) is carried out taking the rotor ends into consideration. Here, the field system equations are derived using the cylindrical model with applying Maxwell's field equations. It is expected that, both starting and maximum torques will increase with taking the rotor ends than that without rotor ends. A simple model is used to establish the geometry of the rotor ends current density and to investigate the air gap flux density. The magnetic flux is assumed to remain radially constant through the very small air gap length between the sleeve and stator surfaces. Variation of the field in the radial direction is ignored and the skin effect in the axial direction is considered. The axial distributions of the air gap flux density, the sleeve current density components and the force density have been determined. The motor performance is carried out taking into account the effects of the rotor ends on the starting and normal operations. The sleeve rotor resistance and leakage reactance have been obtained in terms of the cylindrical geometry of the machine. These equivalent circuit parameters have been calculated and plotted as functions of the motor speed with and without the rotor ends.